Antiferromagnetic insulatronics: Spintronics in insulating 3d metal oxides with antiferromagnetic coupling - Meer, H.; Gomonay, O.; Wittmann, Angela; Klaeui, M. (Applied Physics Letters, 2023)
Antiferromagnetic transition metal oxides are an established and widely studied materials system in the context of spin-based electronics, commonly used as passive elements in exchange bias-based memory devices. Currently, major interest has resurged due to the recent observation of long-distance spin transport, current-induced switching, and THz emission. As a result, insulating transition metal oxides are now considered to be attractive candidates for active elements in future spintronic devices. Here, we discuss some of the most promising materials systems and highlight recent advances in reading and writing antiferromagnetic ordering. This article aims to provide an overview of the current research and potential future directions in the field of antiferromagnetic insulatronics.
CRIS-Team Scopus Importer:2023-03-27